Perancangan Sistem Pemesanan Tiket Bus Pada PT. Betahamu Dengan Metode Design Thinking - Hutauruk, David; Pakpahan, Sorang (KAKIFIKOM (Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer), 2025)
The ticket ordering system carried out at PT. Betahamu still manually, not using the website. Passengers must visit the Betahamu bus counter to find out the departure schedule, purchase tickets and ticket prices on inter-city buses, namely PT. Betahamu, which results in passengers not getting tickets and departure delays because there is no information regarding the number of buses operating on a predetermined schedule, which takes a lot of time and money, does not rule out the possibility of errors. Ticket order report at PT. Your beta is also not recorded neatly. This is the basis for the author to build a web-based information system to make it easier for passengers to order tickets, as well as helping PT. Betamu in managing order data to make it more organized.